'On the outskirts of the Empire': Joseph Brodsky and Lithuania. Issue 3 (3rd July 2017) - Klots, Yasha
ABSTRACT: This article explores the role of Lithuania in Joseph Brodsky's life and works before and after his exile from Russia in 1972. As a former Soviet republic, Lithuania represented an intermediary space for Brodsky both culturally and geographically, contributing to his realization that it was a 'rehearsal' for his actual emigration. However, Brodsky's notion of Lithuania changes when, after 1972, instead of representing a simulacrum of the 'abroad, ' the poet sees Lithuania as a 'home' from afar. Emigration, in Brodsky's case, thus became a realization of the myth of exile implicit in his earlier texts about Lithuania.